Women In East Sumba Society Based On A Human Rights Perspective - Brenda Avila Chandra; Frans Simangunsong (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study examines the protection and fulfillment of women's rights in East Sumba society from a human rights perspective. The focus of the study is directed at various forms of gender inequality that are still influenced by social structures, traditional culture, and power relations that impact women's access to education, health, social participation, and legal protection. The study uses an empirical juridical method with a legislative and socio-cultural approach. Data were obtained through literature studies, analysis of laws and regulations, and a study of social practices that have developed in East Sumba society. The results show that women still face various obstacles in obtaining their rights equally, even though they are normatively guaranteed by national and international human rights instruments. This article analyzes the gap between legal norms and social reality and identifies factors that influence the effectiveness of women's rights protection. The research findings indicate the need for policy strengthening, increasing public legal awareness, and synergy between the government, traditional institutions, and the community to realize more effective and equitable protection of women's rights in East Sumba.